Effect of expanded polytetrafluoroethylene thickness on paclitaxel release and edge stenosis in stent graft - Zhu, Qing; Ye, Ping; Niu, Haifeng; Chang, Zhaohua (Frontiers in Bioengineering and Biotechnology, 2022)
Stent grafts have been widely used to treat lower extremity arterial stenosis or occlusion. However, there are major issues with edge stenosis and loss of patency over time. Paclitaxel-coated stent grafts have been proven to be effective in preventing edge stenosis, but the insufficient amounts of paclitaxel released may limit the effectiveness of drug-eluting stent grafts. In this study, we examined whether paclitaxel-coated expanded polytetrafluoroethylene (ePTFE) stent graft thickness influences paclitaxel release properties and inhibits edge stenosis. Low-, medium-, and high-thickness paclitaxel-coated stent grafts were prepared by varying the thickness of inner and outer ePTFE layers. Surface morphologies of the stent grafts were analyzed using a scanning electron microscope. The stent grafts were then implanted in the iliac arteries of 20 healthy swine. Twelve pigs were used to assess edge stenosis, and digital subtraction angiography was performed at day 30 (n=4), 90 (n=4), and 180 (n=4). Histological evaluation of the treated arteries was also performed. Eight pigs were used for pharmacokinetic analysis, and the treated arteries were obtained at day 1 (n=2), 30 (n=2), 90 (n=2) and 180 (n=2). Scanning electron microscopy confirmed that the mean pore size of the stent grafts decreased with increasing thickness. The results of angiographic and histological evaluation demonstrated that low-thickness ePTFE-stent grafts resulted in edge stenosis and apparent intimal hyperplasia at 180 days, whereas for medium-thickness ePTFE-stent grafts, no obvious edge stenosis and intimal hyperplasia was noted in the similar time period. The results of pharmacokinetic evaluation showed that at 180 days, the paclitaxel concentration of treated arteries of the medium group was 36±53 ng/g, while concentrations in the low group was not detectable. Stent grafts with increased ePTFE thickness appear to allow for more delayed release of paclitaxel compared to low-thickness ePTFEs.